Associations Between Sensorimotor Impairments in the Upper Limb at 1 Week and 6 Months After Stroke. Issue 3 (July 2016) - Meyer, Sarah; De Bruyn, Nele; Krumlinde-Sundholm, Lena; Peeters, Andre; Feys, Hilde; Thijs, Vincent; Verheyden, Geert
Abstract : Background and Purpose: Longitudinal information regarding the prevalence of upper limb somatosensory deficits and the association with motor impairment and activity limitations is scarce. The aim of this prospective cohort study was to map the extent and distribution of somatosensory deficits, and to determine associations over time between somatosensory deficits and motor impairment and activity limitations. Methods: We recruited 32 participants who were assessed 4 to 7 days after stroke, and reassessed at 6 months. Somatosensory measurements included the Erasmus-modified Nottingham sensory assessment (Em-NSA), perceptual threshold of touch, thumb finding test, 2-point discrimination, and stereognosis subscale of the NSA. Evaluation of motor impairment comprised the Fugl-Meyer assessment, Motricity Index, and Action Research Arm Test. In addition, at 6 months, activity limitation was determined using the adult assisting hand assessment stroke, the ABILHAND, and hand subscale of the Stroke Impact Scale. Results: Somatosensory impairments were common, with 41% to 63% experiencing a deficit in one of the modalities within the first week and 3% to 50% at 6 months. In the acute phase, there were only very low associations between somatosensory and motor impairments ( r = 0.03-0.20), whereas at 6 months, low to moderate associations ( r = 0.32-0.69) were found for perceptual threshold of touch, thumb finding test, and stereognosis with motor impairment and activity limitations. Low associations ( r = 0.01-0.29) were found between somatosensory impairments in the acute phase and motor impairments and activity limitations at 6 months. Discussion and Conclusions: : This study showed that somatosensory impairments are common and suggests that the association with upper limb motor and functional performance increases with time after stroke. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A138 ). Abstract : Supplemental Digital Content is Available in the Text.